Partisipasi Masyarakat Dalam Kebijakan Anggaran Daerah - I Wayan Sutrisna (Universitas Mahendradatta Denpasar, 2018)
The budget policy made by the government in principle aims to fulfill the wishes of all levels of society. Budget processes and allocations must be oriented to the public interest. This implies that the budget preparation process should involve many par- ties ranging from planning to implementation. For this reason, it is expected that spending for the public interest gets a greater proportion than spending on the apparatus, because public spending is a government investment that is expected to improve people’s welfare. Participation of all people in regional budget politics is very necessary so that the region- al budget can be used optimally for the development of all the communities in the area. Realizing this participation is not an easy thing because there are still many members of the community who still consider the preparation of regional budgets only determined by officials of the ruling party. The community programs proposed in the Development Planning Consultation (Musrenbang) at the village level will sometimes disappear at the next level because they are not escorted by officials of the ruling party. This assumption is still developing in the community so that the desire to participate in regional budget poli- tics has decreased. This assumption must be eliminated in the midst of the community by all components of the government so that the people want to involve themselves in every process of the formulation of regional budget policies.Participatory of communities are needed in the process of governance and development. The United Nation Development Program (UNDP), an institution under the auspices of the United Nations which deals with the development of nations in the world, has even included community participation in one of the indicators or characteristics of good gov- ernance. This implies that the higher level of community participation in the governance and development process shows that the ruling government has carried out a good gover- nance process.The management of the regional budget by involving high participation from the commu- nity will be able to make all the planning made in preparing the regional budget can be achieved effectively and efficiently. In addition, participatory budget policy will be able to make all programs implemented can be manipulated by all levels of society because all communities feel they have been involved in the entire process. The successful implemen- tation of development in the region will lead to national development success